Application of the decision theory for University Industrial Link (UIL) - Osman, Nor Hasni (2015)
The case was conducted to describe the application of decision theory in determining the best option in selecting source of research grant.The case started with the overview of University Industrial link (UIL) scenario and then looked into the strategic aspect of the collaborations that enable the school to make decision au fait with the needs of the university and social systems.